Staying together - Martin, Ann M., 1955- (New York : Scholastic, 2011)
"It's been two years since Flora and Ruby moved to Camden Falls. They've always gotten along as friends amd as sisters, but now they're starting to fight all the time. Nobody--not their friends, not their grandmother--knows why, or what to do. In the end, it might take a whole town to get them back together and make them realize how much they've grown up since their parents died and their lives changed so much. Staying together isn't easy--but with both friends and sisters, it's the most important thing."- -P. [4] of cover.
Keywords: Sisters -- Juvenile fiction; Grandmothers -- Juvenile fiction; Friendship -- Juvenile fiction